Resepsi Khalayak Terhadap Konten Dakwah Media Sosial NU Lumajang - Dwi Pristanto, Dimas; Ghulam, Zainil (Institut Agama Islam Syarifuddin Lumajang, 2024)
This article discusses the audience's acceptance of content in mass media, in this case social media, managed by NU Lumajang. The manager of NU Lumajang's social media is LTN (Lembaga Ta'lif wa Nasyr) NU Lumajang. The theory used in this study is Stuart Hall's Reception Theory. Also supported by the POACE concept (Planning, Organizing, Actuating, Controlling, and Evaluating) which is commonly used in mass media analysis. This study uses a qualitative method with an analytical reception approach. Data collection techniques are carried out by observing social media content; interviews with NU Lumajang social media managers, interviews with audiences/social media followers, and also strengthened by a survey of forty respondents. The results of this study indicate that every content published in NU Lumajang social media contains messages of da'wah, tarbiyah, cadre formation, and economic strengthening. However, da'wah-themed content is the most frequently created. Some people feel bored with the content published on NU Lumajang social media platforms because it is monotonous. NU Lumajang social media managers must be consistent in creating content and be able to maintain audience trust in existing content. In addition, breakthroughs to improve content must always be made.